PERANCANGAN TAS FUNGSIONAL INLINE SKATE PADA ANAK USIA 8-12 TAHUN - Chyntia Chandra; Gunawan Gunawan; Kumara Sadana Putra (Perpustakaan Universitas Surabaya, 2018)
Abstract – Inline skate is one of the emerging sports in Indonesia, especially among children. This is seen from the binding growth of inline skate community that has spread over 30 communities throughout Indonesia. While going to play, the children carry a variety of inline skate equipment along with their other personal needs so it takes a means of carrying a bag that can meet their needs. The research method used is a mixture that includes literature review, interviews, observation, and behavioral studies. Interviews were conducted with inline skate communities, designers as well as bag manufacturers, parent users, as well as tailor bags. Observations were conducted to find out the inline skate bags on the market, as well as behavioral studies conducted to find out the activities children do when going inline skating. This research produces a prototype in the form of functional bag for inline skating acitivity for children aged 8-12 years. With a compact shape, the bag can adjust the shape of the skates and the storage on the bag can be more leverage, making it easier for children to carry it. Then, the bag is also designed waterproof and ventilated system back so safe to use exercise in the outdoor area. In addition, the product also comes with product management, branding, and cost analysis calculations so that the product is ready to be marketed.